On a Simple Characterization of Conformally Flat 4-Dimensional Spaces of Neutral Signature - KIRIK RÁCZ, BAHAR (My University, 2024)
In this work, the full characterization of 4-dimensional conformally flat spaces of neutral signature is given by using methods based on holonomy structure. Possible holonomy types are obtained for the spaces in question and several remarks are made. Various examples are presented related to this investigation. Keywords: Weyl conformal curvature tensor, Conformally flat space, Neutral signature, Holonomy
4–Boyutlu Nötr Metrik İşaretli Konformal Düz Uzayların Basit Bir Karakterizasyonu Üzerine
Keywords: Matematik; Diferansiyel Geometri; Temel Bilimler; Mathematics; Differential Geometry; Natural Sciences; Temel Bilimler (Sci); Doğa Bilimleri Genel; Çok Disiplinli Bilimler; Natural Sciences (Sci); Natural Sciences General; Multidisciplinary Sciences; Mantık; Geometri ve Topoloji; Ayrık Matematik ve Kombinatorik; Multidisipliner; Fizik Bilimleri; Logic; Geometry and Topology; Discrete Mathematics and Combinatorics; Multidisciplinary; Physical Sciences; Weyl conformal curvature tensor; Conformally flat space; Neutral signature; Holonomy